A super cross-linked polymer adsorption material containing paired thiol groups and preparation method thereof

By using supercrosslinked polymer adsorption materials containing pair thiol groups, the problem of difficult removal of mercury pollution in water is solved, and efficient and low-cost mercury adsorption effect is achieved, especially in the treatment of highly acidic wastewater.

CN116272906BActive Publication Date: 2024-12-20HARBIN ENG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310351609.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2024-12-20
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove mercury pollution in water, especially because mercury cannot be decomposed by microorganisms, and the preparation cost and low efficiency of traditional adsorbent materials are difficult to meet environmentally friendly and efficient treatment needs.

Method used

The supercrosslinked polymer adsorbent material containing a pair of thiol groups is prepared by using aromatic compounds with disulfide bonds as raw materials, and a pair of thiol groups is generated through reduction reaction to form a supercrosslinked porous polymer group rich in thiol groups. Crosslinked polymers for efficient adsorption of mercury.

Benefits of technology

This material has high efficiency mercury adsorption performance, low cost, simple preparation process and high adsorption capacity. It especially shows obvious advantages in treating highly acidic metal-containing wastewater, and can effectively capture mercury in the water environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272906B_ABST
    Figure CN116272906B_ABST
Patent Text Reader

Abstract

A hyper-crosslinked polymer adsorption material containing paired thiol groups and a preparation method thereof. The present invention relates to an adsorption material and a preparation method thereof, and belongs to the field of environmental protection technology and the technical field of functionalized hyper-crosslinked polymer synthesis. The purpose of the present invention is to solve the technical problem that heavy metals in water, especially mercury, seriously pollute the environment. The present invention reacts an aromatic compound containing a disulfide bond with a crosslinking agent under Lewis acid catalysis to obtain a hyper-crosslinked porous polymer precursor rich in disulfide bonds; after the precursor is reacted with a reducing agent, the disulfide bonds in the precursor are converted into paired thiol groups to obtain a hyper-crosslinked polymer adsorption material containing paired thiol groups. The adsorption material of the present invention has the advantages of simple preparation process, low cost, few by-products, high adsorption efficiency, etc., especially in the treatment of highly acidic wastewater containing metal ions, it has obvious advantages and has broad market prospects. The adsorption material prepared by the present invention is used in the field of adsorbing heavy metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption material and a preparation method thereof, in particular to a hyper-crosslinked polymer adsorption material containing paired thiol groups and a preparation method thereof, belonging to environmental protection technology and the technical field of functionalized hyper-crosslinked polymer synthesis. Background Art

[0002] Mercury is a global pollutant. It is persistent, highly toxic, highly enriched and can be transmitted over long distances. It poses a serious threat to the ecological environment and human health and has been widely concerned. The main threat of mercury pollution is that it cannot be decomposed by microorganisms. In the water environment, inorganic mercury can be converted into more toxic methylmercury under certain conditions. Methylmercury has bioaccumulation and biomagnification effects, which will eventually affect higher fish-eating organisms and human health. Therefore, certain pollution control measures need to be adopted to remove mercury from the water so that it can meet the discharge standards.

[0003] Hg in water 2+ Removal methods include adsorption, chemical reduction, chemical precipitation, ion exchange, solvent extraction and reverse osmosis. Among them, the adsorption method has the characteristics of simple operation, high efficiency and low cost, environmental friendliness and deep treatment, making it a very effective treatment method for mercury-containing wastewater. In the adsorption method, the adsorption material is one of the key factors affecting the adsorption effect. The shape, type and existence form of the adsorption material determine the preparation cost, adsorption process and adsorption efficiency of the material. Developing efficient mercury adsorbent materials with a wide range of applications to reduce the harm of heavy metal elements to the environment is one of the important issues that materials scientists and chemists are currently working on. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem that heavy metals in water, especially mercury, seriously pollute the environment, and to provide a hyper-crosslinked polymer adsorption material containing paired thiol groups and a preparation method thereof.

[0005] The invention discloses a hyper-crosslinked polymer adsorption material containing paired thiol groups. A hyper-crosslinked porous polymer precursor is prepared using an aromatic compound containing disulfide bonds as a raw material. The disulfide bonds in the precursor are cut by a reduction reaction to generate paired thiol groups, thereby obtaining the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0006] The method for preparing the hyper-crosslinked polymer adsorption material containing paired thiol groups is specifically carried out according to the following steps:

[0007] Step 1: under nitrogen protection, adding an aromatic compound containing a disulfide bond to an organic solvent, mixing evenly, then adding a Lewis acid and a cross-linking agent to obtain a mixed solution, heating to perform a hyper-cross-linking reaction, filtering to obtain a generated solid product, performing Soxhlet extraction with methanol, and then vacuum drying to obtain a hyper-cross-linked porous polymer precursor rich in disulfide bonds;

[0008] Step 2: Add a reducing agent and the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 into a solvent, carry out a reduction reaction at a reaction temperature, and then filter to obtain a solid substance, wash, and dry to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0009] The present invention provides a hyper-crosslinked polymer adsorption material containing paired thiol groups and a preparation method thereof. A hyper-crosslinked porous skeleton precursor rich in disulfide bonds is constructed, and the disulfide bonds in the skeleton are reduced to generate adjacent paired thiol functional groups in situ, thereby obtaining a hyper-crosslinked polymer containing paired thiol groups. The hyper-crosslinked polymer is applied to the adsorption of mercury, showing efficient mercury adsorption performance.

[0010] The hyper-crosslinked polymer adsorbent material containing paired thiol groups of the present invention has a large number of micropores and a unique pore structure while containing a large number of paired thiol groups. The paired thiol groups have a highly efficient coordination ability for metal ions such as mercury and exhibit extremely high adsorption capacity. The adsorbent has the advantages of simple preparation process, low cost, few by-products, high adsorption efficiency, etc., and has obvious advantages in treating highly acidic wastewater containing metal ions, and has broad market prospects.

[0011] Beneficial effects of the present invention:

[0012] (1) The hyper-crosslinked polymer adsorption material containing paired thiol groups prepared by the present invention is prepared by Friedel-Crafts alkylation and disulfide bond reduction, which has the advantages of being simple, easy to operate, and reusable;

[0013] (2) The hyper-crosslinked polymer adsorbent material containing paired thiol groups prepared by the present invention has a special pore structure and a large number of thiol groups, and has a highly efficient coordination ability and good adsorption capacity for mercury, and can effectively capture mercury in the water environment.

[0014] The adsorption material prepared by the invention is used in the field of heavy metal adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic diagram of the synthesis of a hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1;

[0016] Figure 2 A nitrogen adsorption-desorption curve diagram of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1;

[0017] Figure 3 is a pore size distribution curve of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1;

[0018] Figure 4This is an infrared spectrum of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1;

[0019] Figure 5 This is an X-ray photoelectron spectrum of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1. DETAILED DESCRIPTION

[0020] Specific implementation method 1: This implementation method is a hyper-crosslinked polymer adsorption material containing paired thiol groups. The material uses an aromatic compound containing disulfide bonds as a raw material to prepare a hyper-crosslinked porous polymer precursor, and the disulfide bonds in the precursor are cut by a reduction reaction to generate paired thiol groups, thereby obtaining a hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0021] Specific embodiment 2: This embodiment is a method for preparing a hyper-crosslinked polymer adsorption material containing paired thiol groups, which is specifically carried out according to the following steps:

[0022] Step 1: under nitrogen protection, adding an aromatic compound containing a disulfide bond to an organic solvent, mixing evenly, then adding a Lewis acid and a cross-linking agent to obtain a mixed solution, heating to perform a hyper-cross-linking reaction, filtering to obtain a generated solid product, performing Soxhlet extraction with methanol, and then vacuum drying to obtain a hyper-cross-linked porous polymer precursor rich in disulfide bonds;

[0023] Step 2: Add a reducing agent and the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 into a solvent, carry out a reduction reaction at a reaction temperature, and then filter to obtain a solid substance, wash, and dry to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0024] Specific embodiment 3: This embodiment is different from specific embodiment 2 in that: the aromatic compound containing disulfide bonds in step 1 includes one or a mixture of diphenyl disulfide, dibenzyl disulfide, 4,4'-dimethyl diphenyl disulfide, bis(thiobenzoyl) disulfide, furfuryl disulfide, 4,4'-dithiodibenzoic acid, methylbenzyl disulfide, 2-thienyl disulfide and 4,4'-dihydroxydiphenyl disulfide. Others are the same as specific embodiment 2.

[0025] Specific embodiment 4: This embodiment differs from specific embodiment 2 or 3 in that: the crosslinking agent in step 1 is one or a mixture of dimethoxymethane, 1,2-dichloroethane, 1,4-p-dichlorobenzyl and 4,4'-dichloromethylbiphenyl. The rest is the same as specific embodiment 2 or 3.

[0026] Specific embodiment 5: This embodiment is different from specific embodiments 2 to 4 in that the Lewis acid in step 1 is one or a mixture of titanium tetrachloride, zinc dichloride, tin tetrachloride, aluminum chloride, ferric chloride, boron trifluoride and trifluoromethanesulfonate. The rest is the same as specific embodiments 2 to 4.

[0027] Specific embodiment 6: This embodiment differs from specific embodiments 2 to 5 in that: in the mixed solution of step 1, the aromatic compound containing disulfide bonds is 1 to 3 parts, the Lewis acid is 2 to 6 parts, and the cross-linking agent is 1 to 32 parts by mass. Others are the same as specific embodiments 2 to 5.

[0028] Specific embodiment 7: This embodiment is different from specific embodiments 2 to 6 in that: the cross-linking reaction temperature in step 1 is 40-80° C. and the reaction time is 24-72 hours. The rest is the same as specific embodiments 2 to 6.

[0029] Specific embodiment eight: This embodiment differs from specific embodiments two to seven in that: the reducing agent in step two is one or a mixture of tris(2-carboxyethyl)phosphine hydrochloride, dithiothreitol, β-mercaptoethanol, glutathione and vitamin C. The rest is the same as specific embodiments two to seven.

[0030] Specific embodiment 9: This embodiment differs from specific embodiments 2 to 8 in that: in step 2, the reducing agent is 1 part by mass, and the disulfide bond-rich hyper-crosslinked porous polymer precursor is 1 part by mass. The rest is the same as specific embodiments 2 to 8.

[0031] Specific embodiment 10: This embodiment differs from specific embodiments 2 to 9 in that the reaction temperature of the reduction reaction in step 2 is 25-40° C. and the reaction time is 1-24 hours. Other aspects are the same as those of specific embodiments 2 to 9.

[0032] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0033] Embodiment 1:

[0034] The present embodiment provides a method for preparing a hyper-crosslinked polymer adsorption material containing paired thiol groups, which is specifically carried out in the following steps:

[0035] Step 1, under nitrogen protection, add 1 part of dibenzyl disulfide, 1 part of 1,4-dichlorobenzyl, 2 parts of anhydrous ferric chloride and 30 parts of 1,2-dichloroethane into a three-necked round-bottom flask by mass, mix well to obtain a mixed solution, heat to 40°C for reaction for 24 hours, then heat to 60°C for reaction for 24 hours, then heat to 80°C for reaction for 24 hours, filter to obtain the generated solid product, use methanol for Soxhlet extraction for 24 hours, and then vacuum dry at 60°C for 12 hours to obtain a disulfide bond-rich hyper-crosslinked porous polymer precursor;

[0036] Step 2: Add 1 part of tri(2-carboxyethyl)phosphine hydrochloride and 1 part of the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 to 30 parts of a solvent, wherein the solvent is a mixture of anhydrous ethanol and water in a volume ratio of 1:2, and carry out a reduction reaction at a reaction temperature of 25°C for 10 hours, then filter to obtain a solid substance, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0037] The hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1 is named HCP-SH, and the hyper-crosslinked porous polymer precursor rich in disulfide bonds is named HCP-DS. The synthetic route is shown in the attached Figure 1 shown.

[0038] The specific surface area of ​​the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1 was measured by BET method and was 37.30 m 2 / g.

[0039] Figure 2 This is a nitrogen adsorption-desorption curve diagram of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1; based on the hysteresis phenomenon in the graph, it can be inferred that the material contains a mesoporous structure.

[0040] Figure 3 This is a pore size distribution curve of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1; from the analysis of the figure, it can be seen that the pore size of most pores in the material is less than 2nm, and the pore size of a small number of pores is between 2 and 50nm.

[0041] Figure 4 This is the infrared spectrum of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1. From the analysis of the spectrum, it is known that 3021cm -1 The peak at 2904 cm-1 is the CH stretching vibration peak of the benzene ring. -1 The peak of CH stretching vibration of methylene is 2615 cm -1 The characteristic peak of thiol is 1602cm -1 and 1493cm -1 698 is the stretching vibration peak of CS.

[0042] Figure 5 This is the X-ray photoelectron spectrum of the hyper-crosslinked polymer adsorbent material containing paired thiol groups prepared in Example 1. From the analysis of the figure, it is known that the characteristic peak at 283.76eV is C1s, the characteristic peak at 531.37eV is O1s, and the characteristic peak at 162.98eV is S2p. It is confirmed that the prepared material contains carbon, oxygen, and sulfur elements. The above analysis results show that the hyper-crosslinked polymer adsorbent material containing paired thiol groups has been successfully prepared.

[0043] Mercury adsorption experimental method: Weigh 50 mg of the prepared hypercrosslinked polymer adsorbent containing paired thiol groups and add it to a 250 ml conical flask containing 50 ml of 100 ppm mercuric chloride solution. After sealing, place the conical flask in an air bath constant temperature oscillator at a temperature of 25°C and a rotation speed of 140 rpm for adsorption for 6 hours. After the adsorption is completed, take out a certain amount of mercuric chloride solution, filter it, and use inductively coupled plasma atomic emission spectroscopy (ICP-AES) to determine the mercury concentration in the mercuric chloride solution before and after adsorption, and calculate the mercury adsorption capacity of the adsorbent material according to formula (1).

[0044] Note:

[0045] Where Q is the adsorption amount (mg / g); C0 is the initial concentration of mercury in the solution (mg / L); C is the concentration of mercury in the solution after adsorption (mg / L); V is the volume of the adsorption solution (L); and m is the mass of the adsorbent added (g).

[0046] The mercury adsorption capacity of the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 1 was measured to be 709.6 mg / g.

[0047] Embodiment 2:

[0048] The present embodiment provides a method for preparing a hyper-crosslinked polymer adsorption material containing paired thiol groups, which is specifically carried out in the following steps:

[0049] Step 1, under nitrogen protection, add 1 part of diphenyl disulfide, 1 part of 1,4-dichlorobenzyl, 2 parts of anhydrous ferric chloride and 25 parts of 1,2-dichloroethane into a three-necked round-bottom flask by mass, mix well to obtain a mixed solution, heat to 40°C for reaction for 12h, then heat to 60°C for reaction for 12h, then heat to 80°C for reaction for 24h, filter to obtain the generated solid product, use methanol for Soxhlet extraction for 24h, and then vacuum dry at 60°C for 12h to obtain a disulfide bond-rich hyper-crosslinked porous polymer precursor;

[0050] Step 2: Add 1 part of tri(2-carboxyethyl)phosphine hydrochloride and 1 part of the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 into a round-bottom flask containing 30 parts of a solvent, wherein the solvent is a mixture of anhydrous ethanol and water in a volume ratio of 1:2, and carry out a reduction reaction at a reaction temperature of 30°C for 6 hours, then filter to obtain a solid substance, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0051] The specific surface area of ​​the hypercrosslinked polymer adsorption material containing paired thiol groups prepared in Example 2 was measured by BET method and was 45.11 m 2 / g. According to infrared spectrum analysis, 3025cm -1 The peak at 2911cm is the CH stretching vibration peak of the benzene ring. -1 The peak of CH stretching vibration of methylene is 2598 cm -1 The characteristic peak of thiol is 1607cm -1 and 1512cm -1 The peak at 673 is the stretching vibration peak of the benzene ring C=C, and the peak at 283.82eV is the stretching vibration peak of CS. According to X-ray photoelectron spectroscopy, 283.82eV is C1s, 531.47eV is O1s, and 163.02eV is S2p. The prepared material contains carbon, oxygen, and sulfur elements. The above analysis results show that the super-crosslinked polymer adsorption material containing paired thiol groups has been successfully prepared. The mercury adsorption capacity of the material was determined to be 557.32mg / g by mercury adsorption experiment.

[0052] Embodiment three:

[0053] The present embodiment provides a method for preparing a hyper-crosslinked polymer adsorption material containing paired thiol groups, which is specifically carried out in the following steps:

[0054] Step 1, under nitrogen protection, add 1 part of dibenzyl disulfide, 3 parts of dimethoxymethane, 2 parts of anhydrous ferric chloride and 20 parts of 1,2-dichloroethane into a three-necked round-bottom flask by mass, mix well to obtain a mixed solution, heat to 40°C for reaction for 24 hours, then heat to 60°C for reaction for 24 hours, then heat to 80°C for reaction for 24 hours, filter to obtain the generated solid product, use methanol for Soxhlet extraction for 24 hours, and then vacuum dry at 60°C for 12 hours to obtain a disulfide bond-rich hyper-crosslinked porous polymer precursor;

[0055] Step 2: Add 1 part of tri(2-carboxyethyl)phosphine hydrochloride and 1 part of the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 into a round-bottom flask containing 20 parts of a solvent, wherein the solvent is a mixture of anhydrous ethanol and water in a volume ratio of 1:2, and carry out a reduction reaction at a reaction temperature of 30°C for 6 hours, then filter to obtain a solid substance, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

[0056] The specific surface area of ​​the hyper-crosslinked polymer adsorption material containing paired thiol groups prepared in Example 3 was 51.21 m 2 / g. According to infrared spectrum analysis, 3030cm -1 The peak at 2897 cm-1 is the CH stretching vibration peak of the benzene ring. -1 The peak of CH stretching vibration of methylene is 2577 cm -1 The characteristic peak of thiol is 1623cm -1 and 1489cm -1 The peak at 692 is the stretching vibration peak of the C=C benzene ring, and the peak at 284.02 is the stretching vibration peak of CS. According to X-ray photoelectron spectroscopy, 284.02eV is C1s, 531.04eV is O1s, and 163.11eV is S2p. The prepared material contains carbon, oxygen, and sulfur elements. The above analysis results show that the super-crosslinked polymer adsorption material containing paired thiol groups has been successfully prepared. The mercury adsorption capacity of the material was determined to be 613.06mg / g by mercury adsorption experiment.

[0057] The above is only a preferred embodiment of the present invention. In addition, a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A hyper-crosslinked polymer adsorption material containing paired thiol groups, characterized in that: Specifically, the following steps are performed: Step 1, under nitrogen protection, 1 part of dibenzyl disulfide, 1 part of 1,4-dichlorobenzyl, 2 parts of anhydrous ferric chloride and 30 parts of 1,2-dichloroethane are added to a three-necked round-bottom flask by mass, mixed evenly to obtain a mixed solution, heated to 40°C for reaction for 24 hours, then heated to 60°C for reaction for 24 hours, then heated to 80°C for reaction for 24 hours, filtered to obtain the generated solid product, subjected to Soxhlet extraction with methanol for 24 hours, and then vacuum dried at 60°C for 12 hours to obtain a disulfide bond-rich hyper-crosslinked porous polymer precursor; Step 2: Add 1 part of tri(2-carboxyethyl)phosphine hydrochloride and 1 part of the disulfide bond-rich hyper-crosslinked porous polymer precursor obtained in step 1 to 30 parts of a solvent, wherein the solvent is a mixture of anhydrous ethanol and water in a volume ratio of 1:2, and carry out a reduction reaction at a reaction temperature of 25°C for 10 hours, then filter to obtain a solid substance, wash with deionized water, and vacuum dry at 60°C for 12 hours to obtain the hyper-crosslinked polymer adsorption material containing paired thiol groups.

Citation Information

Patent Citations

  • Method for recycling metal ions in wastewater by using electric-control ion exchange material

    CN109502706A